Analyzing the Key Drivers of FinTech Adoption among Business Students at Pokhara University: A Two-Stage PLS-SEM-ANN Approach - Karmacharya, Bibek (The Management Review, 2025)
The rapid advancement of financial technology (FinTech) has revolutionized financial services globally, with Nepal experiencing growing adoption driven by digital payment platforms, increasing smartphone penetration, and government initiatives. This study aims to identify the key determinants influencing FinTech adoption among business students at Pokhara University. This study examined FinTech adoption among 320 purposively sampled business students at Pokhara University using a two-stage approach, where PLS-SEM with SmartPLS 3.0 assessed linear relationships, and ANN analysis with SPSS 26 captured nonlinear patterns. The study found that Perceived Ease of Use, Financial Literacy, and Regulatory Awareness & Trust significantly influenced FinTech adoption while Perceived Security & Privacy and Social Influence had no significant impact. The implication of the study is that enhancing user experience, integrating FinTech education into curricula, and strengthening regulatory frameworks are essential for promoting adoption and trust in digital financial services among business students.